Systematic Review of Genetic-Related Risk Factor and Inhibitor Epidemiology in People with Severe Hemophilia a from Africa: A 2023 Update - (:unkn) unknown (My University, 2023)
Background and Aims: Prevalence of factor VIII inhibitors in patients with hemophilia A varies from study to study, ranging from 15% to 30%. The important risk of inhibitor development is factor VIII mutation responsible for hemophilia A. Few studies have reported factor VIII mutations in Africa. The aim of this study was to review on FVIII gène mutations of severe hemophilia A in Africa and those associated with inhibitor development. Study Design and Methodology: A systematic review was carried out using the electronic databases Pubmed, Science Direct, Index Medicus Global and African Journals online and the key words "hemophilia A", "inhibitor", "genetic" and "Africa". Studies written in French or English on the African continent and published between 2012 and 2023 were included. Publications relating to acquired hemophilia and duplicates were excluded. In the end, 17 articles were selected. Results: The factor VIII mutations involved in severe hemophilia A in Africa are variable, consisting of intron 22 inversion, large or point deletions, nonsense and missense mutations and splicing abnormalities. Among the latter, numerous previously unrecorded mutations have been identified, and a single case of intron 1 inversion has been found in Algeria. Prevalence of factor VIII inhibitors in severe hemophilia A in Africa varies between 7,8% and 30%. Genetic abnormalities associated with inhibitors include intron 22 inversion, large deletions such as exon 1-13 deletion, nonsense mutations and c.1010-2A>G mutation. Conclusion: A better knowledge of the factor VIII mutations involved in severe hemophilia A in Africa will help improve patient management.
Keywords: African Research